`f(x)= x^(1/3)`

We can use the implicit differentiation to find the derivative

==> `y= x^(1/3)`

Cube both sides

==> `y^3 = x`

Now use implicit differentiation.

==> `3y^2 y' = 1`

Now we will divide by `3y^2` .

==> `y'= 1/(3y^2)`

Now we will substitute with `y= x^(1/3)`

`==gt y'=...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f(x)= x^(1/3)`

We can use the implicit differentiation to find the derivative

==> `y= x^(1/3)`

Cube both sides

==> `y^3 = x`

Now use implicit differentiation.

==> `3y^2 y' = 1`

Now we will divide by `3y^2` .

==> `y'= 1/(3y^2)`

Now we will substitute with `y= x^(1/3)`

`==gt y'= 1/(3(x^(1/3))^2) `

`==gt y'= 1/(3x^(2/3))`